Anti-inflammatory and cytotoxic specialised metabolites from the leaves of Glandularia × hybrida. (March 2022) - Mohamed, Nesma M.; Ahmed, Mai A.M.; Khan, Shabana I.; Fronczek, Frank R.; Mohammed, Anber F.; Ross, Samir A.
Abstract: In our ongoing effort to investigate active specialised metabolites from genus Glandularia, phytochemical studies on the ethanolic extract of Glandularia × hybrida (Groenl. & Rümpler) G.L. Nesom & Pruski leaves resulted in the isolation of three undescribed compounds, a dibenzylbutyrolactolic lignan and two echinocystic acid based triterpenoid saponins, in addition to two known compounds. Interestingly, this study reports isolation of chemo-systematically valuable specialised metabolites for the first time from the genus under investigation. Additionally, the isolated metabolites were evaluated for their iNOS inhibition and cytotoxic activities using a combination of in silico and in vitro studies. The pharmacokinetics properties (ADMET) of some of the isolated compounds were determined using pkCSM-pharmacokinetics server. Molecular docking analysis showed that saponin compound possesses higher negative score (−9.59 kcal/mol) than the lignan compound (−6.56 kcal/mol). The isolated compounds also showed iNOS inhibition activity with IC50 values ranging between 6.6 and 49.7 μM and significant cytotoxic activity against a series of cell lines including SK-MEL, KB, BT-549, SK-OV-3, LLC-PK1 and VERO cells. Hence, this study reveals that specialised metabolites from G. hybrida plant are of significant anti-inflammatory and cytotoxicity potentials. Graphical abstract: Image 1 Highlights: Isolation of three undescribed compounds from Glandularia × hybrida leaves with chemo-taxonomical significance. Molecular docking of the isolated compounds to study their potential as iNOS inhibitors. Determination of pharmacokinetics properties (ADMET) of some of the isolated compounds. Isolated compounds were evaluated for their cytotoxic and iNOS inhibitory activities.